Administration of Iodized Salt, Counseling about Food Sources of Iodine and Goitrogenic, to Mothers who have Children in Primary School, Affect the Excretion of Urine Iodine - I Ketut Swirya Jaya; Iswari Pauzi (Humanistic Network for Science and Technology (HNST), 2018)
To overcome the problem of iodine deficiency, administration of iodized salt, counseling of iodized food sources and goitrogenic food are very important. The goal is to change the consumption of iodized and goitrogenic food sources and consume the recommended iodized salt, so that iodine intake is fulfilled and urinary iodine excretion becomes normal. This study was an experimental research, using pre-test and post-test with control group design. The sample size was 60 students of elementary school, consisting of 30 students. students for the treatment group and 30 students for the control group. In the treatment group, the mothers of the students were given iodized salt to give to their children, provided counseling about food sources that are rich in iodine and which are goitrogenic. The parameters measured were the consumption of iodine, protein and urinary iodine excretion in the phase before and after being treated, with a span of time for 3 weeks. Data collection on nutrient consumption was done through recall once in 24 hours. The level of iodine in the urine was measured using spectrophotometry, and the consumption of goitrogenic sources was measured through observation at the time of recall. The data were analyzed using t-test. Based on the results of the study it can be concluded that in Sedau Village, Narmada District, West Lombok Regency; giving iodized salt, counseling about iodized and goitrogenic food sources to mothers who have children in primary school. Keywords: iodized salt; counseling; food sources of iodine; goitrogenic; excretion of urine iodine